OPTIMALISASI E-CONTRACT (KONTRAK ELEKTRONIK) DALAM PERDAGANGAN INTERNASIONAL DITINJAU DARI PERSPEKTIF HUKUM POSITIF INDONESIA - Tompul, Verawati BR (Jurnal Ilmiah Publika, 2023)
This study is to analyze the validity of electronic contracts in transactions in international trade in terms of positive law in Indonesia. This study is based on the results of a descriptive normative legal study using a legal approach. Types and sources of legal materials used are secondary data. The results of the study show that the validity of electronic contracts in e-commerce transactions with the payment method must meet the provisions of Article 1320 of the Civil Code regarding the terms of the validity of the agreement. In e-commerce transactions to conduct international trade, the terms of validity in Article 1320 of the Civil Code are very difficult to fulfill, so contracts born in e-commerce transactions with payment methods via are invalid and can canceled through a court decision if the parties or one of the parties so wish, but if the parties do not ask for cancellation then the contract remains valid and binding on the parties involved. The responsibilities of each party involved in this transaction, namely the seller, the buyer, the payment system operator, and the expeditionary party, must be viewed in terms of the obligations of each party and also in terms of the loss caused by the fault of the parties involved.